Mobile gadget among teens as social media integration and entertainment preservation of traditional games - Hashim, Mohd Haizra; Ahmad, Abdul Mua'ti @ Zamri; Abd Latif, Muhammad Pauzi; Mohd Yunos, Mohd Yazid (2016)
Malaysian traditional game was a popular culture once, before the existence of foreign and virtual games. Nowadays, the activities of playing traditional games are getting lesser and there are insufficient efforts in preserving or recreating the game. Furthermore, today's teenagers fascination towards mobile foreign games endangered the existence of traditional game. Traditional games are one of our unique traditional cultural assets. However, the force of globalization has resulted in values of foreign cultures been absorbed through the mobile gadget. This would indirectly erode the local cultural values, especially among teenagers. Local teens are now more familiar with the use of mobile gadgets and more should be done to apply the values of the local games, especially traditional games. Mobile gadget is indeed the latest culture technology that can be used as a media to introduce youth to local culture using approaches that are easy, simple and fun.